Multiattribute Nonlinear Utility Theory - Fishburn, Peter C. (Management Science, 1984)
Independence axioms similar to those proposed for multiattribute von Neumann–Morgenstern linear utility theory are examined in the context of new nonlinear utility theories developed by Chew and MacCrimmon, and Fishburn. These new theories weaken the independence axiom of von Neumann and Morgenstern, and Fishburn's theory does not require preferences to be transitive. The paper shows that axioms for independence between attributes lead to decompositions of utility for the nonlinear theories that are related to standard decompositions for linear utility.